P1_6 Red TARDIS - Mahon, Hannah; Reed, Lisa; Fitzpatrick, Amber; Vanderpump, Phoebe (Physics Special Topics, 2022)
In this paper we investigated the effect the relativistic effect would have on the TARDIS from the the BBC television programme Doctor Who. We aimed to calculate the speed at which the TARDIS would have to travel in order to appear red rather than its iconic blue colour. We found that the TARDIS would have to be travelling at 1.3 x 108m/s (2 s.f) away from an observer to appear red. We felt this was a reasonable speed for the spaceship to be travelling at due to it’s advanced time and space travelling capabilities.